(untitled) (Research, Society and Development, 2021)
The job market has diverse demands in terms of professionals, at the same time that people seek qualification to find a place where their skills can be applied and valued. However, people with disabilities and disorders usually face serious difficulties and prejudices to enter the labor market and fully develop their autonomy. In Brazil, Law 8,213/91 (also called the Quota Law) provides that, in companies with 100 or more employees, people with disabilities occupy 2 to 5% of vacancies in companies. In this context marked by the need for integration of individuals in the labor market and the demand for the application of the Quota Law, the objective of this article is to present how was the participation of an individual with Asperger Syndrome in a real work environment during the execution of various activities. The individual is a regular student of the Association of Parents and Friends of the Exceptional (APAE) in the city of Bambuí/MG and has been participating since 2017 in a special training program in computer tools in the institution’s own laboratory. The activities were carried out by the student at the Federal Institute of Minas Gerais (IFMG), Campus Bambuí, for two weeks and made it possible to apply various contents previously studied in the training offered, as well as helping to improve their autonomy and self-confidence.